Iraq and Rockffler Institution for Charity 1929 - 1944 - حيدر حميد رشيد (College of Education for Women, 2019)
The thirties and the early forties and the at end of the World War II of the last century witnessed several attempts carried out by the Public Health Directorate and by the Iraqi Ministry of Foreign Affairs to persuade the Rockefeller Foundation to fund Iraq with its health program which is carried out in several regions in the world to promote the health and social situations since Iraq during that period in history was badly in need to such plans and programs because of this lack of financial and technical possibilities necessary for the advancement of health and social dire situation. The details of these attempts are deposited in the documents of the diplomatic mail records of the United States of America , and documents of the Middle East, Iraq 1925- 1944 saved in the Iraqi National Library and Archive. We were able to obtain unique information and it was a catalyst for us to fathom there where were no signs of this information here and there. Overall, these documents are a correspondence conducted between the Iraqi Ministry of Foreign Affairs and the Rockefeller Foundation for charity by the US Office in Baghdad. The research finds out that the view that Iraq was largely hopeful to be included in the Rockefeller Foundation for charity programs for the advancement of its own health deteriorated situation , and it seems that the global economic crisis that hit the United States of America in the thirties of the last century had the impact on the Rockefeller Foundation for charity and its preoccupation with the activities of supporting the US military in the years of World war II , as well as a the engagement of the foundation with the implementation of the Foundation charitable projects in various regions of the world has hampered the inclusion of Iraq to their programs in the health field operations.